Opera jako forma narracji historycznej - Markiewicz, Grzegorz (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2015)
In the second half the 16th century, in Florence, group gathering specialists in the arts, enthusiasts of the antiquity, composers and poets, called Camerata, put examining the ancient culture for herself behind the target. Resurrecting an ancient Greek musical theatre was a basic task of those fans of the antiquity. An opera is a result of those treatments. From very beginning of the creation of the kind, operatic work sought the inspiration in the past. At first they referred to the classical mythology. Then to medieval history and modern history and national mythology. For centuries librettos were the best way of acquainting Europeans with the ancient legacy, history and the European culture. New historiography is combining historiography with literature, emphasizing all at the same time that history isn’t an image of the past. According to Hyden Whte the historical discourse is interpretation. Paul Ricoeur is convincing that a structural sameness is characterizing historiography with the fictional story. One and second are different ways of the narration. Historiography is writing the story which is talking about facts. Similarly is with the opera, being one of the most compound artistic kinds, since is combining features of the, dramatic and musical literary work which manifest itself in the form of the libretto, the music and the drama. Opera is writing and telling a story.